2003
DOI: 10.1097/00008571-200311000-00003
|View full text |Cite
|
Sign up to set email alerts
|

ABCB1 C3435T and G2677T/A polymorphism decreased the risk for steroid-induced osteonecrosis of the femoral head after kidney transplantation

Abstract: Advances in transplantation technology have brought about great benefits to patients suffering from organ failure, but the problem still remains of complications induced by steroids used for post-transplant immunosuppression. Among the side-effects caused by steroids, non-traumatic osteonecrosis of the femoral head (ONF) constitutes a serious problem. The same protocol for steroid administration induces ONF in some patients, but not in others, indicating the presence of individual difference in steroid sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
63
1
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(72 citation statements)
references
References 22 publications
7
63
1
1
Order By: Relevance
“…This SNP may therefore be linked to a high prevalence of colon cancer in the Ashkenazi population. Similarly, refractory Crohn's disease has also been found to be associated with the 2677G>T/A/C, 3435C>T, and 1236C>T SNPs [31]. This could also be linked to a high prevalence of the disease in the Ashkenazi Jewish population, as noted by the high prevalence of the 3435T allele discovered in our Ashkenazi population.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…This SNP may therefore be linked to a high prevalence of colon cancer in the Ashkenazi population. Similarly, refractory Crohn's disease has also been found to be associated with the 2677G>T/A/C, 3435C>T, and 1236C>T SNPs [31]. This could also be linked to a high prevalence of the disease in the Ashkenazi Jewish population, as noted by the high prevalence of the 3435T allele discovered in our Ashkenazi population.…”
Section: Discussionsupporting
confidence: 66%
“…The 1236C>T and 2677G>T/A/C polymorphisms have also been linked to several diseases such as pharmacoresistant epilepsy and Parkinsons disease [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45]. Studies on these polymorphisms have yielded contradictory results, possibly due to small sample sizes and the isolated nature of the study populations.…”
Section: Discussionmentioning
confidence: 99%
“…HIV The final study 73 examined the relationship between osteonecrosis of the femoral head (ONF) associated with steroid therapy following renal transplantation, and the 3435C4T and 2677G4TA genotypes. The study included 30 patients with ONF and 106 without ONF, all of whom had undergone renal transplantation and post-transplant immunosuppression with tacrolimus or cyclosporine plus either 'large-dose' or 'small-dose' steroid protocols.…”
Section: Effects Of Genotype On Clinical Outcomes Related To Drug Thementioning
confidence: 99%
“…Another limitation of many of these studies 18,96,42,61,69,[72][73][74][77][78][79]84,88,89 was the absence of any attempt to detect or prevent stratification between cases and controls, either through control for ethnicity or genetic methods of detection of stratification (some studies may have been performed in ethnically homogenous populations, but this was not stated). Indeed in two of the studies, significant differences in allele frequency between groups of different ethnicity were commented upon, 42,79 and this was not taken into account when performing the statistical analysis.…”
Section: Limitations Of Studies Of Therapeutic Drug Response and Recomentioning
confidence: 99%
“…[3][4][5][6] However, the relationship of genetic polymorphism of plasminogen activator inhibitor (PAI)-1 4G/5G and post-renal transplant FHON was controversial. 3,5 Nitric oxide (NO) is a multifunctional biomolecule and serves as an important signal in physiologic processes including angiogenesis, thrombosis, and bone turnover, which are known to be related to the pathogenesis of osteonecrosis. 7 It was reported that the predominant isoform of nitric oxide synthases expressed in normal adult bone is endothelial nitric oxide synthase (eNOS).…”
Section: Introductionmentioning
confidence: 99%